Assessment of suitable dose of calcium silicate to rice and its impact on soil properties in laterite soils of Odisha - Das, Aliva; Samant, Prasanna Kumar; Jena, Bandita; Dwibedi, Sanat Kumar; Patra, Ranjan Kumar; Sarangi, Dillip Ranjan (ORYZA-An International Journal of Rice, 2022)
A field experiment was conducted in the central farm, Regional Research and Technology Transfer Station, Coastal Zone OUAT, Bhubaneswar during kharif 2020 using cv-Lalat variety of rice. The experiment was laid out in randomized block design (RBD) with ten treatments and three replications. In this experiment, Basic Oxygen Furnace (BOF) slag was used as a source of silica for application in rice crop. 200, 300 and 400 kg SiO2ha-1 was applied in combination with 50% Soil Test Dose (STD) and 75% STD in order to assess the efficacy of Silica with reduction in fertilizer dose by 50% and 25%. The result indicated that there was significant increase in number of effective tillers per plant and length of the panicle, but no significant increase was observed in case of 1000 grain weight over control. In case of grain yield, straw yield and harvest index, 100% STD registered maximum (36.9q/ha) grain yield which was 29.4% more than that of control. In case of 50% or 75% STD with 300kg SiO2ha-1 grain yield was at par with 100% STD, which indicated that silica application has the capability to reduce the fertilizer dose. Harvest index was not significantly affected by Si treatments. However, maximum HI (0.478) was observed in 75% STD + 300 kg SiO2ha-1. The present study showed increase in pH and organic carbon content in post-harvest soil which suggests that application of silica has the capacity to correct soil acidity and improve soil organic carbon in acidic laterite soils.